The nexus between spirituality and personal financial behavior: a study of students with entrepreneurial intentions - Jatin Jangid; Bhawana Bhardwaj; Dipanker Sharma (LBS Journal of Management & Research)
Purpose – The current study explores the relation between students' spiritual quotient (SQ) and personal financial planning (PFP). The students with entrepreneurial intentions were considered for the present study. Design/methodology/approach – The students from higher educational institutes with an intention to be entrepreneurs were considered for data collection. Using a well-designed, closed-ended questionnaire, primary data from college and university students was collected. Using quota sampling, a total of 189 responses were gathered, however the responses of students with entrepreneurial intentions (n = 100) were considered for analysis. To investigate the relationship between PFP and SQ, descriptive analysis, Spearman's rank correlation and forecasted trend line were employed. Findings – The study revealed a significant positive relationship between PFP and SQ. Thus, SQ also has potential to determine individuals' investment behavior. The study suggests that students' spiritual development can determine their PFP and entrepreneurial actions. Practical implications – The outcome of the study can be practically used to explore the investment pattern and behavior of youth. The study would further benefit the stakeholders including issuers, developers and consultants involved in the creation and distribution of financial products. The study guides researchers to undertake further research in this domain. Originality/value – The existing literature on personal financial behavior has lacked in establishing a relationship between spirituality and investment decisions. The present study is novel in substantiating this void. We contribute to the advancement of literature in behavioral finance. This study identifies multifaceted factors that shape investors' behaviors and preferences in finance and proposes the avenues for future research.